Long-chain base kinase1 affects freezing tolerance in Arabidopsis thaliana. (June 2017) - Huang, Xiaozhen; Zhang, Yao; Zhang, Xiaoyan; Shi, Yiting
Highlights: Loss of function of LCBK1 resulted in decreased tolerance to cold stress in Arabidopsis . Overexpression of LCBK1 improved freezing tolerance in transgenic Arabidopsis plants. Transcriptome analyses suggested that LCBK1 acts in ROS homeostasis and lipid metabolism. Abstract: Long-chain base kinases (LCBKs) phosphorylate sphingolipid-derived long-chain base lipids and participate in the regulation of stress responses in plants. Here, we isolated a novel Arabidopsis thaliana mutant, lcbk1-2, which was extremely sensitive to freezing temperatures with or without cold acclimation. Physiological assays revealed that concentrations of osmolytes (proline and soluble sugars) and the activity of superoxide dismutase were significantly decreased in the lcbk1-2 mutant, compared with wild type. Also, the balance of reactive oxygen species (ROS) was disrupted in the lcbk1-2 mutant with or without cold treatment and, consistent with this, gene expression profiling analysis showed that the expression of cold-responsive ROS-scavenging genes was substantially decreased in the lcbk1-2 mutant. The expression of membrane lipid-related genes, which are linked to freezing tolerance in plants, was also impaired in the lcbk1-2 mutant. Furthermore, transgenic lines overexpressing LCBK1 showed enhanced freezing tolerance with over-accumulation of osmolytes. Collectively, our results suggested that LCBK1 functions as a novel positive regulator of freezing tolerance in Arabidopsis and may participate in the accumulation of osmolytes, the regulation of ROS homeostasis and lipid metabolism.